Benefit of adjuvant radiotherapy after breast‐conserving therapy among elderly women with T1‐T2N0 estrogen receptor‐negative breast cancer. Issue 19 (21st June 2016) - Eaton, Bree R.; Jiang, Renjian; Torres, Mylin A.; Kahn, Shannon T.; Godette, Karen; Lash, Timothy L.; Ward, Kevin C.
Abstract : BACKGROUND: The purpose of the current study was to evaluate the impact of radiotherapy (RT) among women aged ≥ 70 years with T1‐2N0 estrogen receptor (ER)‐negative breast cancer using Surveillance, Epidemiology, and End Results (SEER)‐Medicare‐linked data. METHODS: The study included 3432 women, 2850 of whom received and 582 of whom did not receive RT after breast‐conserving surgery. Outcomes were estimated by the cumulative incidence method and compared with the Gray test. The Fine and Gray subdistribution hazard regression models were used to assess the impact of RT and other variables. RESULTS: Women who received RT were more commonly aged <75 years (42% vs 16%), had T1 tumors (78% vs 65%), ductal carcinoma histology (91% vs 88%), a Charlson‐Deyo Comorbidity Index of 0 (41% vs 25%), and had received chemotherapy (29% vs 12%). The 5‐year cumulative incidence of mastectomy and breast cancer‐specific death for patients who received versus those did not receive adjuvant RT was 4.9% and 8.3% versus 10.8% and 24.1%, respectively ( P <.001). On multivariable analysis, the omission of RT was found to be an independent predictor of an increased risk of mastectomy (hazard ratio, 2.33; 95% confidence interval, 1.56‐3.49). Among women aged ≥ 80 years or with T1N0 tumors, the mastectomy incidence with or without receipt of RT was 3.4% vs. 6.9%, and 5.3% vs 7.7%, respectively. CONCLUSIONS: The use of adjuvant RT after breast‐conserving surgery in older women with T1‐2N0 estrogen receptor‐negative breast cancer is associated with a reduced incidence of future mastectomy and breast cancer death. The magnitude of benefit may be small for women aged ≥80 years or those with T1 tumors. Cancer 2016;122:3059‐3068 . © 2016 American Cancer Society . Abstract : In this Surveillance, Epidemiology, and End Results (SEER)‐Medicare analysis of 3432 women aged ≥ 70 years with T1‐2N0 estrogen receptor‐negative breast cancer, the use of adjuvant radiotherapy after breast‐conserving therapy was associated with a significantly reduced incidence of mastectomy and breast cancer death. However, among the subgroup of women aged ≥80 years or with T1N0 tumors, the absolute difference in the incidence of mastectomy with or without receipt of radiotherapy was small.